200k views
4 votes
Which could be the first step in solving the equation represented by the model below?

3x + 4 = 2x + 6

a. add 4 negative unit tiles to both sides.
b. add 4 negative unit tiles to the left side, and add 6 negative unit tiles to the right side.
c. add 4 positive unit tiles to both sides.
d. add 6 negative unit tiles to the left side, and add 4 negative unit tiles to the right side.

User High
by
4.8k points

1 Answer

6 votes
The answer is A

Explanation-
3x + 4= 2x + 6
-4 = -4
3x=2x + 4
-2x= -2x

X=4
User Ususer
by
4.7k points